(untitled) (Althea Medical Journal, 2015)
Background: Sexually transmitted infections (STIs) are major health problem. Until today, the prevalence of STIs is still high and the incidence is increasing. Almost half of STIs new cases occur in adolescents andyoung adults. It is assumed that there is a positive correlation of knowledge about STIs with attitude and practices; therefore, giving proper information of STIs to adolescents could influence their safe sexual practices, and further, it can prevent STIs to occur. The objective of this study is to discover knowledge and attitude of senior high school students in Jatinangor towards STIs. Methods: This descriptive study was conducted in Sekolah Menengah Atas Persatuan Guru Republik Indonesia (SMA PGRI) Jatinangor and Sekolah Menengah Atas Negeri (SMAN) Jatinangor from May to September 2013. Questionnaires were completed by 278 respondents selected by stratified cluster random sampling. Results: More than half respondents had poor knowledge about STIs (56.5%) while 53.2% of the respondents had positive attitude towards STIs. Most mentioned choices as the information source of STIs were teacher (66.5%), followed by television/radio (45.3%), friends (37.8%), newspaper/magazine (21.2%), mother (16.2%), sibling (7.2%), and father (6.5%). Conclusions: More detail information about STIs is needed by adolescents as a way to encourage safe sexual practices. Teacher and parents are expected to be the source information of STIs while mass media can also be used to educate adolescents. Education on STIs for teachers is also needed since they are as the main source for educating the adolescents. [AMJ.2015;2(4):568–74] DOI: 10.15850/amj.v2n4.655